Hubungan Keterampilan Bertanya Guru dengan Motivasi Belajar Siswa Kelas V SDN 1 Dasan Baru Tahun Ajaran 2021/2022 - Rahmawati, Rina; Darmiany, Darmiany; Saputra, Heri Hadi (Pendagogia: Jurnal Pendidikan Dasar, 2022)
This study aims to find out if there is a relationship between the skills of asking teachers and the motivation of learning students of class V SDN 1 dasan New School Year 2021/2022. This research is quantitative research with correlational methods. The population in the study is students of class V SDN 1 Dasan Baru numbering 61 students. The sample used in this study was quota sampling so researchers used 30 students as research samples. The data collection technique in this study used questionnaires. The data is analyzed with the help of SPSS version 16. The description of the teacher's asking skills level and student learning motivation was analyzed using descriptive analysis, and for the hypothesis test the study was analyzed using the Perason Product Moment formula with the help of SPSS version 16. Rhitung value of 0.669 then large rtabel 0.361 in the level of significance of 5% which means there is a significant and positive relationship between the teacher's questioning skills and the motivation of learning students grade V. Based on the interpretation guidelines on the coefficient of Sugiyono (2018: 257) the rhitung value of 0.669 is at intervals 0.60-0779 shows a strong relationship.